PENGEMBANGAN BAHAN AJAR MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN PKN KELAS V SEKOLAH DASAR BERORIENTASI TEKNIK KLARIFIKASI NILAI - Aka, Kukuh Andri; Sahari, Sutrisno (Universitas Nusantara PGRI Kediri, 2017)
This study aims to develop interactive multimedia on Civic Education learning oriented value clarification techniques that are valid, practical, effective, and interesting for students. Interactive multimedia is selected to maximize available technological facilities, innovate learning and enhance learning attractiveness. Value clarification techniques are used to innovate a series of learning steps on interactive multimedia and can be used to train students to discover, select, analyze, decide, take on their own values ​​of life they want to fight for. The material on this multimedia is about legislation. The models used in this development study are modification of Borg & Gall (1987) and Lee & Owen (2004) models. Through expert validation and product trials, this interactive multimedia is included in valid criteria (4,60), practical (4,53), attractive (4,31), and effective (85,2). For further product development, it should be innovated with strategies or other learning models and different materials. Keywords: interactive multimedia, Civic, value clarification techniques